Osvrt na Tišmin prevod Kertesovog romana "Besudbinstvo" (Philologia, 2021)
This paper analyses the Serbian translation of the novel Fateless, written by one of the most prolific contemporary Hungarian novelists Imre Kertész, who was awarded the Nobel prize in 2002. As the translator himself (Aleksandar Tišma) was one of the most prominent Yugoslav writers, and was in many ways similar to Kertész, an effort was made to prove that this translation is unique, especially compared to those usually produced by professional literary translators. Since one of the most important stylistci traits of Imre Kertész lies in his non-conventional use of language, the main question is how the translator managed to stay faithful to the seemingly very simple and non-grammatical language production of Kertész's narrator, a 15-year-old boy from Budapest who finds himself in a Nazi concentration camp.